Special abilities and qualities of young fencers aged 10-12 as criteria for success in sports - Victoriya Klymenchenko; Iryna Kryventsova; Michał Chamera (Pedagogy of Health)
Background and purpose. The success of young athletes depends on many personality characteristics and elements of the training system. The purpose of the study is to identify the most significant special abilities and qualities of young fencers aged 10-12 years old at the initial stage of training.